Droplets spectrum of air-assisted boom sprayers under different environmental and operational conditions - Robson S. Sasaki; Mauri M. Teixeira; Haroldo C. Fernandes; Sérgio Zolnier; Christiam F. S. Maciel; Cleyton B. de Alvarenga (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT During pesticide spraying, the psychrometric conditions of the air may cause evaporation of the droplets along their trajectory from the nozzle to the target. Thus, this study aimed to evaluate the effect of air psychrometric conditions and operating pressure on the droplet spectrum of air-assisted boom sprayers. The test was performed using a prototype equipped with an axial fan, a flow homogenizer, temperature and relative air humidity sensors, a spray nozzle and a gas-heating system to warm up the airflow. With the assembled system and the aid of a particle analyser, the JSF 11002 spray nozzle was evaluated with respect to droplet spectrum in four air psychrometric conditions (7, 14, 21 and 28 hPa) and at four operating pressures (200, 300, 400 and 500 kPa). At the end, evaporation losses were observed during the sprayings. For a given operating pressure and for each increment of 1 hPa in vapor pressure deficit, there was a diameter reduction of approximately 0.0759, 0.518 and 1.514 μm for the parameters DV0.1, DV0.5 and DV0.9, respectively. The diameter of the droplets decreased as the operating pressure increased.